A new species of Forcepsioneura Lencioni, 1999 in honor to Queen Elizabeth II (Odonata: Protoneuridae) - Lencioni, F. A.a. (Zootaxa, 2022)
A new species of Forcepsioneura Lencioni, 1999 is described from seven males and three females (Holotype ♂ (FAAL NC 4521), Brazil, São Paulo, Monteiro Lobato—SP, 22° 57’ 19’’ S & 45° 50’ 27’’ W, 653 m, 28.xi.2010). The new species is compared with F. itatiaiae (Santos, 1970) its closest congener. Diagnostic illustrations are presented. The main differences between Forcepsioneura species are: in females, the posterior lobe of the prothorax and in males the shape of cerci and the posterior lobe of the prothorax. The species is named Forcepsioneura elizabethae sp. nov. in honor of Her Majesty Queen Elizabeth II on the occasion of her platinum jubilee.